Influence of the Centaurs and TNOs on the main belt and its families - Galiazzo, Mattia A.; Wiegert, Paul; Aljbaae, Safwan [UNESP] (Springer Nature, 2016)
Centaurs are objects whose orbits are found between those of the giant planets. They are supposed to originate mainly from the Trans-Neptunian objects, and they are among the sources of Near-Earth Objects. Trans-Neptunian Objects (TNOs) cross Neptune’s orbit and produce the Centaurs. We investigate their interactions with main belt asteroids to determine if chaotic scattering caused by close encounters and impacts by these bodies may have played a role in the dynamical evolution of the main belt. We find that Centaurs and TNOs that reach the inner Solar System can modify the orbits of main belt asteroids, though only if their mass is of the order of 10 − 9m⊙ for single encounters or, one order less in case of multiple close encounters. Centaurs and TNOs are unlikely to have significantly dispersed young asteroid families in the main belt, but they could have perturbed some old asteroid families. Current main belt asteroids that originated as Centaurs or Trans-Neptunian Objects may lie in the outer belt with short lifetime ≤4My, most likely between 2.8 and 3.2 au at larger eccentricities than typical of main belt asteroids.
Keywords: Asteroids: general – celestial mechanics; Minor planets